2019
DOI: 10.1080/19336950.2019.1674242
|View full text |Cite
|
Sign up to set email alerts
|

Voltage vs. Ligand I: Structural basis of the intrinsic flexibility of S3 segment and its significance in ion channel activation

Abstract: We systematically predict the internal flexibility of the S3 segment, one of the most mobile elements in the voltage-sensor domain. By analyzing the primary amino acid sequences of V-sensor containing proteins, including Hv1, TPC channels and the voltage-sensing phosphatases, we established correlations between the local flexibility and modes of activation for different members of the VGIC superfamily. Taking advantage of the structural information available, we also assessed structural aspects to understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 154 publications
(178 reference statements)
3
17
0
Order By: Relevance
“…Notably, we found a good correlation between S3 flexibility indices and the sensitivity to temperature (measured as the Q 10 coefficient) so that if the channel exhibits high sensitivity to heat, local S3 helix become more rigid and vice versa. On the other hand, we also reported a good correlation between the degree of S3 flexibility and activation by mechanical stretching [7]. In the present study, we extend our analysis exploring the origins of the 6TM channels and we found that in one of the more ancient bacterial lineages (Aquificae) the only transport protein with significant similarity to members of the 6TM members of the VGIC superfamily corresponds to a putative potassium channel (kch) protein (ORF Aq1863) [10].…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…Notably, we found a good correlation between S3 flexibility indices and the sensitivity to temperature (measured as the Q 10 coefficient) so that if the channel exhibits high sensitivity to heat, local S3 helix become more rigid and vice versa. On the other hand, we also reported a good correlation between the degree of S3 flexibility and activation by mechanical stretching [7]. In the present study, we extend our analysis exploring the origins of the 6TM channels and we found that in one of the more ancient bacterial lineages (Aquificae) the only transport protein with significant similarity to members of the 6TM members of the VGIC superfamily corresponds to a putative potassium channel (kch) protein (ORF Aq1863) [10].…”
Section: Introductionsupporting
confidence: 75%
“…In total, 32 sequences were included in this study ( intestinalis (NP_001071937); ehHv1 from Emiliania huxleyi CCMP1516 (005762299); kHv1 from Karlodinium veneficum (AEQ59286); mHv1 from Mus musculus (NP_083028); TAX-4 from Caenorhabditis elegans (CAB63418); Shaker K V channel from Drosophila melanogaster (CAA29917); CNGA1 from Homo (P29973), and CNGA2 from M. musculus (Q62398). Estimation of flexibility indices has been described in the companion study [7].…”
Section: Data Assembly and Local Flexibility Predictionmentioning
confidence: 99%
See 3 more Smart Citations